Information and communication technologies as systemic tools of the rebuilding strategy of Ukraine's infrastructure in the context of European integration (Economics and region, 2024)
The article explores the strategic role of information and communication technologies (ICT) as systemic tool of the rebuilding strategy of Ukraine's infrastructure in the context of European integration. It emphasizes that ICT is not only an element for technological advancement but also a key factor in strengthening Ukraine’s socio-economic potential and overcoming the consequences of the Russian invasion. The research outlines the importance of ICT in optimizing resource management, enhancing coordination, and facilitating the digital transformation of various sectors, such as energy, transportation, and public services. By integrating ICT, Ukraine can increase the efficiency of rebuilding critical infrastructure, streamline decision-making processes, and improve the accessibility of government services. The research highlights several challenges Ukraine faces in the ICT sector, including cybersecurity risks, limited internet access in rural areas, gaps in digital literacy among different population groups, and reduced foreign investments due to the war. These issues are critical to address in order to ensure the successful implementation of digital technologies across the country. The article also draws attention to the European Union’s experience in digital development. Furthermore, the article notes that the country’s IT sector demonstrated resilience during the war and could play a significant role in the post-war recovery, especially by leveraging the growing international support and cooperation with global tech industries. The article highlights the importance of strengthening cybersecurity to protect critical infrastructure and sensitive data from potential cyberattacks, especially in the context of ongoing conflict. The research points out that Ukraine must focus on ensuring secure digital environments, protecting personal and financial information, and fostering digital literacy to combat misinformation and maintain the resilience of its information systems. The conclusion emphasizes that ICT has the potential to become a central pillar in Ukraine’s recovery and long-term development. The successful implementation of digital technologies can enhance not only economic growth but also social inclusion and governance.
Keywords: information and communication technologies; strategic tools; infrastructure; innovations; communication infrastructure; post-war recovery